Validation and Refinement of Salmonella pullorum (SP) Colored Antigen for Diagnosis of Salmonella Infections in the Field - Muktaruzzaman, M.; Haider, M.G.; Ahmed, A.K.M.; Alam, K.J.; Rahman , M.M.; Khatun, M.B.; Rahman, M.H.; Hossain, M.M. (International Journal of Poultry Science, 2010)
Salmonella infections are major problems for the poultry farming in Bangladesh. The cultural method to identify avian Salmonella infections is laborious and expensive, thus a rapid, sensitive and cost-effective method for the diagnosis of salmonellosis is anticipated. In the present investigation Salmonella pullorum organisms was obtained from the Department of Pathology and it was characterized by culture, biochemical tests and PCR. A neotetrazolium stained Salmonella pullorum antigen was prepared from local isolate of Salmonella pullorum. The protein concentration of stained antigen was measured by BSA standard curve. Prepared antigen was diluted in 2 fold dilution and minimum 72.5 μg/μl antigen concentration showed the positive reaction. Different preservatives (0.5% phenolized saline, 0.5% formalized saline and 0.09% sodium azide) were used to maintain the shelf life of prepared antigen. All the preservatives showed the similar results up to six months. Slide agglutination tests were carried out with un-diluted and diluted anti-sera having known ELISA titre and end point agglutination titre was determined. Serum titre 13942-21362 gave positive result to 2-5 fold dilution of serum and serum titre 412-771 showed negative result. Different groups of antigens were developed while antigen group-1 (48 h bacterial culture treated with 24 h in neotetrazolium and 2 h in thiomersal) gave the striking positive result. As Group-1 antigen exhibited highest protein concentration (1240 μg/μl) and gave the best result with positive sera, so it was selected for field trial. The seroprevalence of Salmonella infection was 44.39% in a particular poultry farm. The stained antigen was then stored at 4oC. As all used preservatives revealed similar trend of results, so it may be recommend that 0.5% phenolized saline as preservative because it is cost effective. In the present study, the slide agglutination test was found easy, sensitive, reliable, cost and time effective and needed very small amount of antigen, sera and as well as accessories. Salmonella pullorum antigen from a local isolate was successfully developed which could be used to screen the Salmonella infection in the poultry flocks at the farm premises. It may also be used to determine the antibody titer of the vaccinated flocks.